2011
DOI: 10.1090/s0002-9939-2010-10555-5
|View full text |Cite
|
Sign up to set email alerts
|

Two questions on mapping class groups

Abstract: Abstract. We show that central extensions of the mapping class group M g of the closed orientable surface of genus g by Z are residually finite. Further we give rough estimates of the largest N = N g such that homomorphisms from M g to SU(N ) have finite image. In particular, homomorphisms of M g into SL([ √ g + 1], C) have finite image. Both results come from properties of quantum representations of mapping class groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…This result improves a result of L. Funar [4] which shows that homomorphisms from the genus g ≥ 1 mapping class group to GL(n, C) have finite image provided n ≤ √ g + 1.…”
Section: Introduction and Statement Of Resultssupporting
confidence: 86%
“…This result improves a result of L. Funar [4] which shows that homomorphisms from the genus g ≥ 1 mapping class group to GL(n, C) have finite image provided n ≤ √ g + 1.…”
Section: Introduction and Statement Of Resultssupporting
confidence: 86%
“…On the other hand, it has been also shown by Bridson (see [6]) that M g,n has only finitely many irreducible linear representations over any algebraically closed field, up to dimension (g + 1). Later, Funar [15] showed that there is no linear representation with infinite image up to dimension about √ g + 1. However, there is an obvious linear representation of rank 2g which comes from the action of M g,n on the homology of Σ g,0 (the map θ g,n defined below).…”
mentioning
confidence: 99%
“…The first result on the nonexistence of faithful linear representations of the mapping class group was obtained by Farb-Lubotzky-Minsky [2] who proved that no homomorphism from a subgroup of finite index of the mapping class group into GL(n, C) is injective for n < 2 √ g − 1. This was improved first by Funar [8] who showed that every map from the mapping class group into SL(n, C) has finite image for n ≤ √ g + 1. This was improved further by…”
Section: Introduction and The Resultsmentioning
confidence: 97%